Novel Paramyxovirus Associated with Severe Acute Febrile Disease, South Sudan and Uganda, 2012 - César G. Albariño; Michael Foltzer; Jonathan S. Towner; Lory A. Rowe; Shelley Campbell; Carlos M. Jaramillo; Brian H. Bird; DeeAnn M. Reeder; Megan E. Vodzak; Paul Rota; Maureen G. Metcalfe; Christina F. Spiropoulou; et al. (Emerging Infectious Diseases, 2014)
In 2012, a female wildlife biologist experienced fever, malaise, headache, generalized myalgia and arthralgia, neck stiffness, and a sore throat shortly after returning to the United States from a 6-week field expedition to South Sudan and Uganda. She was hospitalized, after which a maculopapular rash developed and became confluent. When the patient was discharged from the hospital on day 14, arthralgia and myalgia had improved, oropharynx ulcerations had healed, the rash had resolved without desquamation, and blood counts and hepatic enzyme levels were returning to reference levels. After several known suspect pathogens were ruled out as the cause of her illness, deep sequencing and metagenomics analysis revealed a novel paramyxovirus related to rubula-like viruses isolated from fruit bats.